Stereopsis after anterior temporal lobectomy. (September 2016) - Verhoef, Bram-Ernst; Decramer, Thomas; van Loon, Johannes; Goffin, Jan; Van Paesschen, Wim; Janssen, Peter; Theys, Tom
Abstract: Brain areas critical for stereopsis have been investigated in non-human primates but are largely unknown in the human brain. Microelectrode recordings and functional MRI (fMRI) studies in monkeys have shown that in monkeys the inferior temporal cortex is critically involved in 3D shape categorization. Furthermore, some human fMRI studies similarly suggest an involvement of visual areas in the temporal lobe in depth perception. We aimed to investigate the role of the human anterior temporal neocortex in stereopsis by assessing stereoscopic depth perception before and after anterior temporal lobectomy. Eighteen epilepsy surgery patients were tested, pre- and postoperatively, in 3 different depth discrimination tasks. Sensitivity for local and global disparity was tested in a near-far discrimination task and sensitivity for 3D curvature was assessed in a convex-concave discrimination task, where 3D shapes were presented at different positions in depth. We found no evidence that temporal lobe epilepsy surgery has a significant effect on stereopsis. In contrast with earlier findings, we conclude that local as well as global stereopsis is maintained after unilateral resection of the temporal pole in epilepsy surgery patients. Our findings, together with previous studies, suggest that in humans more posterior visual regions underlie depth perception.